Alcohol Increases Impulsivity and Abuse Liability in Heavy Drinking Women - Reed, Stephanie Collins (2012)
Heavy drinking has increased in recent years and has been linked to numerous health-related risks, particularly in women. A number of factors may play a role in exacerbating the risks linked to heavy drinking, such as impulsivity, which itself is related to a number of risky behaviors. The present study investigated the effects of alcohol (0, 0.5, 0.75 g/kg) on impulsivity in female heavy drinkers (n = 23) and female light drinkers (n = 23) using a double-blind, placebo-controlled outpatient design; all women were tested during follicular phase of the menstrual cycle. Each session, participants completed a range of tasks including subjective measures of abuse liability, cognitive performance tasks, three behavioral impulsivity tasks, and a risk-taking task. Alcohol increased impulsivity on the Immediate and Delayed Memory Task (IMT and DMT) and Delay Discounting task. Heavy drinkers scored higher on impulsivity self-reports and were more impulsive on the IMT and the GoStop task than light drinkers. The high dose of alcohol further increased impulsive performance on the IMT and DMT in heavy drinkers. There were no group differences or alcohol effects on the Balloon Analogue Risk Task. Alcohol increased sedative-like effects more in light drinkers and increased stimulant-like effects and alcohol liking more in heavy drinkers. In summary, female heavy drinkers are less sensitive to the negative effects of alcohol, report more positive effects of alcohol, and are more impulsive than female light drinkers. Moreover, impulsive responding was exacerbated by alcohol drinking among female heavy drinkers, indicating that women who drink at this level are at increased risk for developing alcohol use disorders and engaging in other risky behaviors, particularly after drinking.